2005
DOI: 10.1371/journal.pgen.0020025.eor
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ribosomal Protein Gene Structures: Implications for Intron Evolution

Abstract: Many spliceosomal introns exist in the eukaryotic nuclear genome. Despite much research, the evolution of spliceosomal introns remains poorly understood. In this paper, we tried to gain insights into intron evolution from a novel perspective by comparing the gene structures of cytoplasmic ribosomal proteins (CRPs) and mitochondrial ribosomal proteins (MRPs), which are held to be of archaeal and bacterial origin, respectively. We analyzed 25 homologous pairs of CRP and MRP genes that together had a total of 527… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Roy and Hartl (2006) studied two relatively closely related Plasmodium species and found a very slow rate of intron loss and possibly no gain during ∼100 Myr of evolution. On the other hand, these results contrast with estimates from fungi (Nielsen et al 2004) and more distantly related eukaryotic clades (Fedorov et al 2002;Rogozin et al 2003;Babenko et al 2004;Roy and Gilbert 2005c;Yoshihama et al 2006), which suggest prevalence of intron gain over intron loss over periods >200 Myr.…”
Section: Rates Of Intron Loss and Gaincontrasting
confidence: 87%
See 2 more Smart Citations
“…Roy and Hartl (2006) studied two relatively closely related Plasmodium species and found a very slow rate of intron loss and possibly no gain during ∼100 Myr of evolution. On the other hand, these results contrast with estimates from fungi (Nielsen et al 2004) and more distantly related eukaryotic clades (Fedorov et al 2002;Rogozin et al 2003;Babenko et al 2004;Roy and Gilbert 2005c;Yoshihama et al 2006), which suggest prevalence of intron gain over intron loss over periods >200 Myr.…”
Section: Rates Of Intron Loss and Gaincontrasting
confidence: 87%
“…However, ours and other studies in closely related species show a pattern of recurrent intron loss, particularly in highly expressed housekeeping genes that are most likely to recombine with their reverse transcribed cDNA. Because of their high degree of conservation at both sequence and functional levels, such genes are the ones most often used in gene structure comparisons (Rogozin et al 2003;Yoshihama et al 2006). The process of loss is likely to be much more accelerated in organisms with high reproductive rates and large population sizes where selection for reduced transcript length, rather than genetic drift, will lead to fixation of losses in populations.…”
Section: Rates Of Intron Loss and Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…3). This general strategy can be modified to account for the possibility that general preferences in intron insertion (e.g., into protosplice sites) and/or intron phase biases (reviewed in Rogozin et al 2012) could lead to independent intron insertions occurring at homologous positions in different lineages (Sverdlov et al 2005;Yoshihama et al 2006). Avariety of studies have shown that genes from intron-rich species from any major eukaryotic supergroup share a significant number of intron positions with other groups (Fedorov et al 2002;Rogozin et al 2003;Csurös et al 2008Csurös et al , 2011.…”
Section: Reconstruction Of Intron-exon Structures In Lecamentioning
confidence: 99%
“…Ribosomal protein is a group of organella involving in cell structure and cell cycle, and possess the important ability to control cell growth, differentiation and adherence. The ribosomal protein is certainly related to cell energy or substance metabolism, and has critical physiological roles in nutrient transport [31] . HBV PS1TP5 protein also interacts with Homo sapiens inositol monophosphatase 2 (IMPA2), Homo sapiens solute carrier family 7 member 5 (SLC7A5), Homo sapiens cytochrome c oxidase subunit 8A, Homo sapiens enolase 1, Homo sapiens H3 histone family 3B, Human cytoskeletal gamma-actin gene, Homo sapiens eukaryotic translation elongation factor 1, Homo sapiens epoxide hydrolase 1, Homo sapiens dehydrogenase 1, Homo sapiens signal sequence receptor-β, Homo sapiens β5-microtubulin and Homo sapiens pyruvate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%